A Comparison of Creatinine, Cystatin C, and Creatinine‐Cystatin C Based Equations in HIV/AIDS Patients: A Cross‐Sectional Study - Kweku Amoah Ampiah; Richard Afari; Jude Osei‐Assibey; Ramseyer Asamoah; Amos Acheampong; Lawrence Dzata; Joseph Kyei‐Mensah; Linda Ahenkorah‐Fonjo; Samuel A. Sakyi; Albert Abakah‐Yawson; Gabriel Pezahso Kotam; Richard K. D. Ephraim (Health Science Reports)
ABSTRACT Background and Aim Chronic kidney disease (CKD) is becoming prevalent among people living with HIV/AIDS infection, with kidney dysfunction progressing to end‐stage kidney disease (ESKD). We tested the diagnostic performance of creatinine, cystatin c, and the combined (creatinine + cystatin c)‐based estimated glomerular filtration rate (eGFR) in assessing kidney dysfunction in HIV/AIDS patients on stable antiretroviral therapy (ART) at the Saltpond District Hospital, Ghana. Methods A cross‐sectional study of 100 HIV/AIDS patients on ART at the Saltpond District Hospital was conducted. Anthropometric data (height, waist circumference, and weight), blood pressure, and demographic and socioeconomic characteristics were obtained from all enrolled participants through questionnaires. Venous blood was collected for creatinine and cystatin estimation. Urine was also collected and a spot test for micro‐albuminuria was performed. Results Our study revealed a mean serum creatinine level of 82.60 ± 21.69 with serum creatinine within the normal range for both female and male participants. The eGFR‐Scr seems to have a better eGFR/CKD classification performance than the eGFR‐Scys‐c and eGFR combined (Scr + Scys). At similar cut‐off values, eGFR‐Scr + Scys showed the greatest diagnostic performance in HIV/AIDS patients, with the largest AUC (AUC = 0.91) in the ROC plot with a sensitivity of 100% and specificity of 11%. Conclusions The combined (Scr + Scys) based eGFR equation has the best diagnostic performance in predicting kidney insufficiency/CKD in HIV/AIDS patients on ART. Serum cystatin c‐based estimated glomerular filtration (eGFR‐Scr) equation is better for assessing kidney function for patients with eGFR< 60 mL/min/1.73 m2, and eGFR‐Scr based equations are better in eGFR/CKD classification and staging.